2020
DOI: 10.1590/1516-3180.2019.0524.05032020
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cross-cultural adaptation and validation of the Finnish Diabetes Risk Score (FINDRISC) for use in Brazilian Portuguese: questionnaire validity study

Abstract: INTRODUCTION Recently, the International Diabetes Federation reported that the number of individuals with type 2 diabetes mellitus (T2DM) had increased worldwide, especially in Brazil, which placed this country in fifth place among the countries with the most people with diabetes mellitus. 1 Given this reality, strategies are being sought in an attempt to easily and cost-effectively screen individuals with high potential to develop T2DM, in order to implement preventive measures against the onset of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several risk scores have been derived worldwide either as a new original tool like ADADRT [6], FINDRISK [7], CANRISK [8], GDRS [9], and AUSDRISK [10] or by translation and adaptation of the original tool in different population. The FINDRISK and CANRISK were translated and calibrated to be used among Brazilians [16,17]. The ADADRT was translated and validated among the Malaysians [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several risk scores have been derived worldwide either as a new original tool like ADADRT [6], FINDRISK [7], CANRISK [8], GDRS [9], and AUSDRISK [10] or by translation and adaptation of the original tool in different population. The FINDRISK and CANRISK were translated and calibrated to be used among Brazilians [16,17]. The ADADRT was translated and validated among the Malaysians [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the Brazilian Portuguese language, the FINDRISC tool is available to tracking the risk of developing DM2 11 . Comparing the results of the Brazilian version of the FINDRISC versus CANRISK, we observed that both have acceptable measurement properties, with ICC values >0.90, kappa values >0.40, Cronbach's alpha values >0.75, and significant correlations (p<0.05) with other instruments already validated in the Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian Diabetes Risk Questionnaire (CANRISK), originally created and validated in Canada, was developed by the Public Health Agency of Canada with the aim of identifying the risk of prediabetes or DM2 10 . In Brazil, there is a questionnaire with the objective of also tracking the risk of developing DM2, called the FINDRISC 11 . However, the CANRISK presents more items that may be related to the risk of developing DM2, such as ethnicity and educational level.…”
Section: Introductionmentioning
confidence: 99%
“…• Rastrear o risco de DM e estimular a adoção de medidas para prevenção do aparecimento de DM2, principalmente m pessoas com risco aumentado para a doença 38 Satisfação e avaliação da qualidade dos cuidados em DM…”
Section: (Continuação)unclassified
“…Questionários para o diabetes validados para o Brasil tem sido um aliado na triagem de diversas outras doenças, e para tanto, no Brasil temos dois instrumentos disponíveis38,44 .Finalmente, os desafios de viver com a DM1 para as crianças e adolescente, são muitos e os profissionais de saúde precisam compreendê-los, assim como as estratégias de enfrentamento, a fim de auxiliarem crianças e suas famílias na melhor condução do tratamento e a se adaptarem a uma nova forma de viver. As crianças vivenciam situações estressantes ao longo do tratamento que afetam o convívio social e familiar, tendo em vista que a terapêutica para controle da doença implica em limitações de atividades, seguimento de dieta específica, submissão a procedimentos dolorosos, alterações corporais e repetidas internações hospitalares 72 .…”
unclassified